TINGKAT KEBERLANJUTAN LAHAN SAWAH DI KELURAHAN SETIANAGARA, KECAMATAN CIBEUREUM, KOTA TASIKMALAYA, JAWA BARAT - Anggia Adita Mawarsari; Trisna Insan Noor (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Agricultural development in Indonesian faces the problem of land resource scarcity due to the increased conversion of agricultural land. Various attempts were made to maintain the availability of paddy fields, one of them was to establish the LP2B (Sustainable Food Agricultural Land) policy. One of the areas included in the LP2B area is Setianagara, Cibeureum District, Tasikmalaya City. This study aims to determine the sustainability level of paddy fields and analyze sensitive factors in influencing the level of sustainability of paddy fields. The design in this study uses quantitative design and survey  methods. The analytical tool used is the Multidimensional Scaling method in the Rap-PaddyField technique. The analysis shows the level of sustainability of the five dimensions (social, economic, environmental, technological, legal and institutional) all included in the less sustainable category. Multidimensional paddy field sustainability index at 38.69% which is included in the less sustainable category. The sensitive factors or attributes that most influence the level of sustainability of multidimensional paddy fields are subsidies, the use of certified local seeds, and affection for the land. This study shows the need for LP2B policies to be realized by noting into sensitive factors of the results of this study.